Prickly pear work at the R. W. Williams Ranch in Dimmit County Texas in the 1960’s - Pluenneke , Ricks H. (Journal of the Professional Association for Cactus Development, 1990)
This paper is dedicated to Mr. Leroy P. Williams, who is my stepfather, and to Dr. Jim Dodd, Texas A&M University, who taught me in graduate school and who conducted research with prickly pear on the R. W. William Ranch near Carrizo Springs, Dimmit County, Texas, during the 1960’s. The paper is based upon recent interviews with these gentlemen and is tempered with personal experience growing upon the ranch during the drought of the 1950’s. The prickly pear cactus referred to in this paper is basically Opuntia lindheimeri now O. engelmanii since 1988. The R. W. Williams Ranch was operated by Mr. Leroy P. Williams at that time.